2018
DOI: 10.21608/jenvbs.2018.3231.1024
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rhizoctonia solani damping-off in Soybean (Glycine max L.) by plant growth promoting rhizobacteria strains

Abstract: Rhizobacteria (PGPR) for its antagonist activity and suppression of Rhizoctonia solani AG2-3 causal agent of damping-off disease in soybean plant. Strains of Bradyrhizobium japonicum 110, Bacillus megaterium var. phosphaticum B6, Methylobacterium aminovorans ML3, M. rhodinum ML12, and Trichoderma viride 1433 species were used in the present study. In vitro, all tested strains showed a notable ability to inhibit mycelial growth of R. solani on different growth media. While, T.viride and M. rhodinum showed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…Biological control introduces several advantages over other types of pathogen control such as: high specificity against targeted pathogens, low cost of production and application as well as ecofriendly. The antagonistic mechanisms through which biological control agent affect pathogens community are variable and not always clear, but generally may be related to one of the following: (1) direct parasitism leading to death of the pathogen; (2) competition on nutrients and space and (3) production of cytotoxic compounds such as antibiotics or toxic volatiles (Heydari and Pessarakli 2010;Omara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biological control introduces several advantages over other types of pathogen control such as: high specificity against targeted pathogens, low cost of production and application as well as ecofriendly. The antagonistic mechanisms through which biological control agent affect pathogens community are variable and not always clear, but generally may be related to one of the following: (1) direct parasitism leading to death of the pathogen; (2) competition on nutrients and space and (3) production of cytotoxic compounds such as antibiotics or toxic volatiles (Heydari and Pessarakli 2010;Omara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The suggested strategy used in this case may by the production of siderophores leading to iron starvation which affect pathogen growth. Previous studies have demonstrated that Trichoderma species can be used as a biocontrol agent in controlling a number of plant diseases with high efficacy (Kucuk and Kivanc 2003;Omara et al 2017Omara et al , 2018Elkhwaga et al 2018). Also, the light microscope image illustrates the possible mechanism used by the Trichoderma to inhibit fungal growth where the affected pathogen mycelia appeared empty from cytoplasm and its component in addition to loss of septation, so it is likely that the mechanism involved in this case is related to the hydrolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To protect against soilborne diseases, it is better to use chemical pesticides in controlling these diseases but, these are expensive as well as not environmental friendly. So, many researchers have used plant growth-promoting rhizobacteria (PGPR) as biological control against late wilt disease associated with the maize rhizosphere which could improve plant health, reduce chemical pesticides, and develop efficient biological control strategies (El-Mehalowy et al 2004 and Ashour et al 2013 ; Omara et al 2017 , 2018 ). Therefore, recently, biological control by PGPR has been adopted on a commercial scale by using a number of experimental approaches.…”
Section: Introductionmentioning
confidence: 99%